2017
DOI: 10.1002/pbc.26784
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and treatment of Langerhans cell histiocytosis patients with central nervous system abnormalities: Current views and new vistas

Abstract: Central nervous system (CNS) involvement in Langerhans cell histiocytosis (LCH) can include mass lesions of the hypothalamic pituitary axis, choroid plexus, cerebrum, and cerebellum or magnetic resonance imaging (MRI) signal abnormalities of the cerebellum, pons, and basal ganglia. The term neurodegenerative (ND) CNS-LCH has been given to the MRI signal abnormalities and neurologic dysfunction, although initially patients may have no clinical symptoms. Standardized evaluations to better understand the natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
74
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 80 publications
0
74
0
5
Order By: Relevance
“…Symmetrical, T2 hyperintense signal changes and hypointense or hyperintense signals on T1 can also be seen in the cerebellar gray matter, pons, basal ganglia, and globus pallidum. 49 These lesions show variable FDG uptake, in contrast to tumefactive lesions, 50,51 and can be asymptomatic or associated with progressive neurologic decline. The term neurodegenerative histiocytosis has been given to the MRI signal abnormalities and neurologic dysfunction associated primarily with LCH; some of these patients may have minimal or no clinical neurologic symptoms.…”
Section: Organ Involvement: Clinical and Radiographic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Symmetrical, T2 hyperintense signal changes and hypointense or hyperintense signals on T1 can also be seen in the cerebellar gray matter, pons, basal ganglia, and globus pallidum. 49 These lesions show variable FDG uptake, in contrast to tumefactive lesions, 50,51 and can be asymptomatic or associated with progressive neurologic decline. The term neurodegenerative histiocytosis has been given to the MRI signal abnormalities and neurologic dysfunction associated primarily with LCH; some of these patients may have minimal or no clinical neurologic symptoms.…”
Section: Organ Involvement: Clinical and Radiographic Characteristicsmentioning
confidence: 99%
“…The term neurodegenerative histiocytosis has been given to the MRI signal abnormalities and neurologic dysfunction associated primarily with LCH; some of these patients may have minimal or no clinical neurologic symptoms. 49 Rosai-Dorfman disease involving the CNS is rare (10%) and involves the dura far more frequently than the brain parenchyma. 31,52 A potential clue to the diagnosis is emperipolesis (lymphocytes engulfed by histiocytes) in spinal fluid.…”
Section: Organ Involvement: Clinical and Radiographic Characteristicsmentioning
confidence: 99%
“…b) For patients with suspected LCH, biopsy is necessary, as LCH may be confused with GCT or other SSR lesions. The diagnosis should also be based on histological and immunephenotypic examinations beyond clinical manifestations and MRI features, which is supported by previous reports (20,26). The main therapy for intracranial LCH is chemotherapy, while a particular regimen should be based on the location and presentation of the lesions.…”
Section: Discussionmentioning
confidence: 61%
“…(2) MRI typically shows isointensity in both T1WI and T2WI (though with low specificity) and obvious homogeneous enhancement. Although previous studies have indicated that MRI of LCH in the hypothalamicpituitary region showed no specific pattern, homogeneous enhancement was usually obvious (20,21); (3) Extrasellar lesions, especially nodules in the bone, would be suggestive; (4) Tumor markers such as AFP and β-HCG are in the normal range or slightly elevated. c) Although CP is the most common cause of SSR masses in children, it does not usually present as CDI, with one report showing that ∼15% of pediatric CP patients present with CDI (22).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation